Isolation and complete genome analysis of Porcine Parvovirus 1 from swine with reproductive failure in southern India - P. Mohanapriya; S. Parthiban; K. Reshma; M. Parthiban; M. Murugan; A. Ramesh; K. Senthilkumar; P. Raja; P. Jalantha; Jagadish Hiremath; S. S. Patil; M. Kalyana Chakravarthi; et al. (Archives of Microbiology, 2026)

Comparison of Pediatric and Adult Glucagon-Like Peptide-1 Receptor Agonist Exposures Reported To United States Poison Centers, 2017–2024 - Anjali Senthilkumar; Hannah L. Hays; Sandhya Kistamgari; Natalie I. Rine; Allison L. Rhodes; Christopher E. Gaw; Gary A. Smith (Journal of Medical Toxicology, 2026)
Introduction As glucagon-like peptide-1 receptor agonist (GLP-1) use has increased among children, a better understanding of the related adverse effects in this population is needed. Methods National Poison Data System data from 2017 to 2024 were analyzed to compare characteristics and trends of exposures involving GLP-1s reported to United States (US) poison centers (PCs) among children 6–17 years old with those of adults. Results There were 13,924 single-substance GLP-1 exposures reported to US PCs from 2017 to 2024. The rate of exposures per one million US population increased by 1,830.8% from 0.97 in 2017 to 18.79 in 2024, including a 4,805.0% increase among children 6–17 years old from 0.04 in 2017 to 1.97 in 2024, with the majority of the increase occurring after 2021. Most exposures (91.7%) were associated with no or mild effects, while moderate effects were observed in 8.0% and major effects occurred in 42 exposures; there were two deaths. Children 6–17 years old were more likely (RR: 2.66, 95% CI: 1.73–4.11) to be admitted than adults, and children 12–17 years old were more likely (RR: 1.68, 95% CI: 1.08–2.63) to experience a more serious medical outcome than adults. Children 6–17 years old with at least one clinical effect experienced vomiting (88.2%) more commonly than adults (61.3%) (RR: 1.44, 95% CI: 1.34–1.55). Additionally, exposures among children 6–17 years old were more likely to be attributable to intentional misuse (RR: 8.12, 95% CI: 6.47–10.17) than among adults. Conclusions This study provides national-level, real-world findings that may help inform clinical practice.

Tailored electrochemical sensing of phenolic pollutant via dysprosium molybdate-infused multi-walled carbon nanotubes for superior detection performance - Dhayanithi Senthilkumar; Chih-Yu Kuo; Norah A. Albassami; Mani Govindasamy (Journal of Water Process Engineering, 2025)

Mitigating pounding through drift limitations: a focus on buildings with re-entrant corner - Ananda Mitra; Shailesh Lahoti; A. Laghate; G. Tamizharasi; R. Senthilkumar (Innovative Infrastructure Solutions, 2025)

Advanced highly precise simultaneous electrochemical detection of toxic azo dyes with Nanoengineered yttrium Iron oxide decorated functionalized carbon nanofibers - Dhayanithi Senthilkumar; Chih-Yu Kuo; Samar A. Aldossari; Mani Govindasamy (Food Chemistry, 2025)

Integrated image segmentation techniques for high-resolution coastal habitat mapping: Advancing remote sensing for coastal ecosystem assessment - Senthilkumar C; Hadeel Alsolai; Randa Allafi; Munya A. Arasi (Journal of South American Earth Sciences, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

K-means Pelican Optimization Algorithm based Search Space Reduction for Remote Sensing Image Retrieval - W. T. Chembian; G. Senthilkumar; A. Prasanth; R. Subash (Journal of the Indian Society of Remote Sensing, 2025)

Evaluating the availability and carbon footprint of agricultural waste ashes: a strategy for achieving sustainable cement production in India - Uma Chandru; A. Bahurudeen; R. Senthilkumar; T. Vijay (Innovative Infrastructure Solutions, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Enhancing rainwater harvesting and groundwater recharge efficiency with multi-dimensional LSTM and clonal selection algorithm - N. Raghava Rao; Sree Pokkuluri Kiran; Tamboli Amena I; A. Senthilkumar; R. Sivakumar; M. Ashok Kumar; Sampathkumar Velusamy (Groundwater for Sustainable Development, 2024)

Mapping of groundwater availability in dry areas of rural and urban regions in India using IOT assisted deep learning classification model - Senthilkumar S; A. Basi Reddy; Anna Alphy; Jayaraj Velusamy; Indra J; Manikandan Rajagopal (Groundwater for Sustainable Development, 2024)

Exploring luminescent carbon dots derived from syrup bottle waste and curcumin for potential antimicrobial and bioimaging applications - Natesan Thirumalaivasan; Kuppusamy Kanagaraj; Kamaraj Logesh; Sridhar Chandrasekaran; Sandeep Kumar; Raghunandhakumar Subramanian; Nangan Senthilkumar; Ashok Kumar; V. Jagadeesha Angadi; Abdullah A. Al-Kahtani (Chemosphere, 2024)

Shrimp classification for white spot syndrome detection through enhanced gated recurrent unit-based wild geese migration optimization algorithm - L. Ramachandran; S. P. Mangaiyarkarasi; A. Subramanian; S. Senthilkumar (Virus Genes, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

BIN1 in the Pursuit of Ousting the Alzheimer’s Reign: Impact on Amyloid and Tau Neuropathology - Ishnoor Kaur; Tapan Behl; G. Sundararajan; P. Panneerselvam; A. R. Vijayakumar; G. P. Senthilkumar; T. Venkatachalam; Dharmender Jaglan; Shivam Yadav; Khalid Anwer; Neeraj Kumar Fuloria; Aayush Sehgal; et al. (Neurotoxicity Research, 2023)

Assessment of solar thermal monitoring of heat pump by using zeolite, silica gel, and alumina nanofluid - G. Antony Casmir Jayaseelan; A. Surenderpaul; T. Thandial Selvam; A. Anderson; A. Senthilkumar; Avinash Malladi; R. Venkatesh; V. N. Aneesh; R. Saravanan (Clean Technologies and Environmental Policy, 2023)

Enhancement of RCCI engine characteristics of Jatropha oil biodiesel as high reactivity fuel and 1-pentanol as low reactivity fuel with variable injection timing - B. Deepanraj; A. Ashok; S.K. Gugulothu; Ragireddy Venkat Reddy; N. Senthilkumar; Zafar Said; Mrinal Bhowmik (Fuel, 2023)

A critical evaluation of additive blended cashew nut shell liquid blended biodiesel performance in compression ignition engine - N. Senthilkumar; Praveen Raj; J. Ranjitha; A. Muniappan (Environment, Development and Sustainability, 2023)

Thidiazuron, a phenyl-urea cytokinin, inhibits ergosterol synthesis and attenuates biofilm formation of Candida albicans - Pandurangan Harikrishnan; Balamani Arayambath; Vijay Karthik Jayaraman; Kanimozhi Ekambaram; Emad A. Ahmed; Palanisamy Senthilkumar; Hairul-Islam Mohamed Ibrahim; Arjunan Sundaresan; Krishnaraj Thirugnanasambantham (World Journal of Microbiology and Biotechnology, 2022)

Isolation and genetic analysis of Porcine circovirus 2 in southern India evidences high circulation of Porcine circovirus 2d genotype - S. Parthiban; A. Ramesh; Anbu Kumar Karuppannan; G. Dhinakar Raj; S. Hemalatha; M. Parthiban; K. Senthilkumar; D. Balasubramaniyam; R. Sumanth Kumar; S. Ranganatha; Chintu Ravishankar (Molecular Biology Reports, 2022)

Molecular evidence of porcine circovirus 3 infection in swine: first report in southern India - S. Parthiban; A. Ramesh; G. Dhinakar Raj; Anbu Kumar Karuppannan; S. Hemalatha; M. Parthiban; Chintu Ravishankar; K. Senthilkumar; D. Balasubramaniyam (VirusDisease, 2022)

Reuse of Uncontrolled Burnt Bagasse Ash from Sugar Industries with Waste Rubber Powder in Construction: A Waste to Wealth Approach for Sugar Mills - K. S. Teja; R. Senthilkumar; G. Athira; A. Bahurudeen (Sugar Tech, 2022)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

A novel approach to preparation of nano-adsorbent from agricultural wastes (Saccharum officinarum leaves) and its environmental application - Durairaj Kaliannan; Senthilkumar Palaninaicker; Velmurugan Palanivel; Mahadik A. Mahadeo; Bulakhe N. Ravindra; Shim Jae-Jin (Environmental Science and Pollution Research, 2019)

Diagnosis of Mycobacterium bovis in Captive Sloth Bears (Melursus ursinus) by Polymerase Chain reaction - M. Veeraselvam; R. Sridhar; T. M. A. Senthilkumar; P. Perumal; M. G. Jayathangaraj (Proceedings of the Zoological Society, 2015)

A Rare Cause of Late-Onset Cerebellar Ataxia: Erdheim–Chester Disease - Senthilkumar V. Shanmugam; Madhan Kolappan; Mamta Garg; Winston J. Rennie; Peter Furness; Yusuf A. Rajabally (The Cerebellum, 2013)

Computational analysis of deleterious missense mutations in aspartoacylase that cause Canavan’s disease - K. Sreevishnupriya; P. Chandrasekaran; A. Senthilkumar; R. Sethumadhavan; V. Shanthi; P. Daisy; J. Nisha; K. Ramanathan; R. Rajasekaran (Science China Life Sciences, 2012)

Evaluation of the cocktail recombinant antigens, LipL32 and LipL41 for serodiagnosis of canine leptospirosis - M. Subathra; T. M. A. Senthilkumar; P. Ramadass; V. Ramaswamy (World Journal of Microbiology and Biotechnology, 2011)

Serodiagnosis of bovine leptospirosis by IgG-Enzyme-Linked Immunosorbent Assay and Latex Agglutination Test - T. M. A. Senthilkumar; M. Subathra; P. Ramadass; V. Ramaswamy (Tropical Animal Health and Production, 2010)

Molecular phylogeny of mangroves VII. PCR-RFLP of trnS-psbC and rbcL gene regions in 24 mangrove and mangrove-associate species - M. Parani; M. Lakshmi; B. Ziegenhagen; M. Fladung; P. Senthilkumar; A. Parida (Theoretical and Applied Genetics, 2000)

Butyltin compounds in sediment and fish from the Polish Coast of the Baltic Sea - Kurunthachalam Senthilkumar; Carolyn A. Duda; Daniel L. Villeneuve; Kurunthachalam Kannan; Jerzy Falandysz; John P. Giesy (Environmental Science and Pollution Research, 1999)

Butyltin Compounds in River Otters (Lutra canadensis) from the Northwestern United States - K. Kannan; R. A. Grove; K. Senthilkumar; C. J. Henny; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1999)

Molecular phylogeny of mangroves V. Analysis of genome relationships in mangrove species using RAPD and RFLP markers - M. Parani; M. Lakshmi; P. Senthilkumar; Nivedita Ram; A. Parida (Theoretical and Applied Genetics, 1998)

Occurrence of Butyltin Compounds in Tissues of Water Birds and Seaducks from the United States and Canada - K. Kannan; K. Senthilkumar; J. E. Elliott; L. A. Feyk; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1998)

Accumulation Features of Polychlorinated Biphenyls and Organochlorine Pesticides in Resident and Migratory Birds from South India - S. Tanabe; K. Senthilkumar; K. Kannan; A. N. Subramanian (Archives of Environmental Contamination and Toxicology, 1998)